WAKIDJO PENGENDHANG HANDAL KLENÃNGAN GAYA SURAKARTA - Risnandar - (Pascasarjana Institut Seni Indonesia Surakarta, 2010)
This article is result ofresearch whichbased on three main questions: Who is Wakidjo? What are the concept and form of his drumming? What are the factors that have influenced the formation and development of Wakidjo’s drumming? This research aims to reveal Wakidjo’s life, his approach to drumming, and his contribution to the world of Solonese style gamelan music, uses a qualitative methodology. Besides drawing on oral accounts from several informants, it also uses literary sources that concern drumming and gamelan musicians. Several psychological theories are used as a basis for writing a profile about Wakidjo. Among others, this project uses convergence theory from William Stren and theory about the development of talent from Monks and Y. Punberg. In order to clarify Wakidjo’s drumming, Rahayu Supanggah’s Bothèken about interpretation is used. This research concludes that Wakidjo’s existence as one of the foremost drummers in Surakarta has been influenced by several factors, including his surroundings, his talent, his performance experience, his predecessors, gamelan associations, the gamelan circle at the National Indonesian Radio Station (RRI) in Surakarta, the world of the recording industry, and the world of gamelan music education.Key word: Wakidjo, Klenengan, Karawitan Instrument